Kajian Tipologi Bangunan pada Pusat Rehabilitasi Mental Disorder - Karlina Rahadatul Aisy; Anisa Anisa (Prodi Arsitektur Universitas Matana, 2020)
This study is aimed to describe typologies in building mental rehabilitation rehabilitation centers. Building typology is obtained through analysis based on form and function. Typological analysis is useful as input in the design of buildings, and rehabilitation center. The research method used is descriptive interpretative qualitative, to get the typology after identifying the activities, functions, and shapes of buildings. As a first step of the patient's activity and space are identified first. The conclusions obtained from the typology study of mental disorder rehabilitation center are the physical arrangement of the rehabilitation center mass: (1) multi-mass and scattered; (2) the zone is divided into several, namely the public in the outermost, semi-public for patient activities, and private for therapy and patient rest. From the physical aspect, it refers to the forms of simple facades, openings that are given a trellis or passive, as well as simple rooms and furniture that do not endangering the patient. In the unstable condition of the patient, an isolation room is controlled by the nurse. In a stable condition, patients can learn a variety of plans which are carried out inside or outside the room.